Eve & Adam : Jewish, Christian, and Muslim readings on Genesis and gender - Schearing, Linda S.; Ziegler, Valarie H., 1954- (Indiana University Press, 1999)
No other text has affected women in the western world as much as the story of "Eve and Adam". The story has engendered countless commentaries, has been used to argue the 'fallen' nature of humankind or to explain or exploit relations between the sexes, and has played a key role in justifying the ways of God toward man and woman. This remarkable anthology surveys more than 2,000 years of Jewish, Christian, and Muslim commentary on the biblical story that continues to raise fundamental questions about what it means to be a man or to be a woman. The selections range widely from early post biblical interpretations in the Apocrypha and Pseudepigrapha to three commentaries written especially for this volume. The editors have included early rabbinic texts, interpretations from the New Testament, and commentaries from the Church Fathers. There are excerpts from the Quran, from medieval Jewish commentaries, from Thomas Aquinas and other later figures, as well as representative texts of the Protestant Reformation. One section focuses on nineteenth-century America and the antebellum debate on slavery, the struggle for women's equality, and new religious movements such as Shakerism and Christian Science. Twentieth century texts from all three traditions conclude the volume. A special appendix focuses on race and Genesis 1-3 at the turn of the new millennium. The tale told through these texts is a remarkable one of the hold the story of "Eve and Adam" has had on the western imagination. The editors note that though the biblical account has been invoked throughout history to justify all manner of oppression, there is an equally rich tradition of egalitarian interpretation, well-represented in this book. Far from a collection of lifeless, historical documents, these texts are lively representatives of a debate that continues to animate men and women to this day
Keywords: Bible. -- Genesis, I-III -- Criticism, interpretation, etc. -- History.; Bible. -- Genesis, I-III -- Criticism, interpretation, etc., Jewish -- History.; Bible. -- Genesis, I-III -- Islamic interpretations -- History.; Eve -- (Biblical figure); Adam -- (Biblical figure); Genesis -- Rezeption.; Adam -- Eva -- Genesis 1-3 -- Exegese.; Eva -- Adam -- Genesis 1-3 -- Exegese.; Genesis 1-3 -- Adam -- Eva -- Exegese.; RELIGION -- Biblical Studies -- Old Testament.; RELIGION -- Biblical Criticism & Interpretation -- General.; Islamic interpretations of sacred works; Schepping.; Genesis (bijbelboek); Sekseverschillen.; Interreligieuze dialoog.; Frau und Mann -- Bibel.; Bibel -- Frau und Mann.; Exegese -- Judentum -- Genesis 1-3 -- Adam -- Eva.; Judentum -- Exegese -- Genesis 1-3 -- Adam -- Eva.; Exegese -- Islam -- Genesis 1-3 -- Adam -- Eva.; Islam -- Exegese -- Genesis 1-3 -- Adam -- Eva.; littérature juive -- Adam et Eve.; littérature chrétienne -- Adam et Eve.; littérature musulmane -- Adam et Eve.; exégèse -- "Bible. AT. Genèse. 1 -- 5"; féminisme -- "Bible. AT. Genèse. 1 -- 5"; Criticism, interpretation, etc.; History